Handbook on public sector efficiency - Afonso, António; Tovar Jalles, João; Venâncio, Ana (Edward Elgar Publishing, 2023)
"Examining the increasingly relevant topic of public sector efficiency, this dynamic Handbook investigates the context of constrained fiscal space and public funding sources using cross-country datasets in areas including China, India, sub-Saharan Africa and OECD economies. Expert contributors evaluate public sector efficiency for both national and sub-national governments, analysing important sectors such as education, health, public-private enterprises and state-owned enterprises. Given voters' requirements to be more educated and for greater accountability on the use of public spending, chapters describe methodology and measurement issues alongside the allocation of resources to ensure better efficiency and effectiveness. Forward-thinking, the Handbook provides insights into how improving efficiency can greatly assist governments when dealing with unforeseen events such as the recent Covid-19 pandemic and the conflict in Ukraine. This Handbook will be an important read for academics and students of public sector economics and public administration and management. It will also provide an excellent background for the policy makers of international institutions looking to help the general public have a better understanding of how public spending works in order for them to make informed decisions when voting"--